Packing chained items in aligned bins with applications to container transshipment and project scheduling - Briskorn, Dirk; Fliedner, Malte (Mathematical methods of operations research (Heidelberg, Germany), 2012)
Bin packing problems are at the core of many well-known combinatorial optimization problems and several practical applications alike. In this work we introduce a novel variant of an abstract bin packing problem which is subject to a chaining constraint among items. The problem stems from an application of container handling in rail freight terminals, but is also of relevance in other fields, such as project scheduling. The paper provides a structural analysis which establishes computational complexity of several problem versions and develops (pseudo-)polynomial algorithms for specific subproblems. We further propose and evaluate simple and fast heuristics for optimization versions of the problem.